Monetary Shocks or Real Shocks, Which matters the most for Share Prices - Subhani, Muhammad Imtiaz (Information Management and Business Review, 2011)
This study examines that out of monetary shocks (âˆ†M2) and real shocks in share prices (âˆ†Yt-k), which one or both really explain share prices of Karachi stock exchange 100 index. The time series econometrics is used to investigate the data for the monthly period of January 1991 to January 2011 for money supply (M2) and share prices of KSE 100 index. The results of unit root test reveal that there is a real shock in share prices and it explains the share price of KSE 100 index temporarily, while Vector auto regression revealed that Share prices of KSE 100 index is meagerly explained by the monetary shocks.